2007
DOI: 10.1055/s-2007-990287
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Consumption of Fermented Soybean-derived Chungkookjang Attenuates Hepatic Insulin Resistance in 90% Pancreatectomized Diabetic Rats

Abstract: Soy protein and isoflavonoids in soybeans exhibit the improvement of insulin resistance. Our previous IN VITRO study showed that Chungkookjang (CKJ), fermented unsalted soybeans, had better antidiabetic actions than cooked unfermented soybeans (CSB) by increasing isoflavones aglycones and small peptides. We investigated whether 40% fat diets with different protein sources such as CSB, CKJ, and casein modulated peripheral insulin resistance in 90% pancreatectomized (Px) diabetic rats. The Px rats weighing 209+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 24 publications
0
35
0
Order By: Relevance
“…Soybean isoflavones have been reported to treat atherosclerosis, cancer, osteoporosis, and others [194]. In addition, soy protein and isoflavonoids in soybeans improve insulin resistance and enhancement of insulin release [195, 196]. Genistein is a key isoflavone present in soybean ( Glycine max ) and other edible plants and has been reported to have anticancer, antioxidant, anti-inflammatory, and antiosteoporosis activities.…”
Section: Selected Medicinal Herbs and Compounds For T2dmentioning
confidence: 99%
“…Soybean isoflavones have been reported to treat atherosclerosis, cancer, osteoporosis, and others [194]. In addition, soy protein and isoflavonoids in soybeans improve insulin resistance and enhancement of insulin release [195, 196]. Genistein is a key isoflavone present in soybean ( Glycine max ) and other edible plants and has been reported to have anticancer, antioxidant, anti-inflammatory, and antiosteoporosis activities.…”
Section: Selected Medicinal Herbs and Compounds For T2dmentioning
confidence: 99%
“…Cheonggukjang fermented with B. subtilis and B. amylofenices had no effect on body weight or adiposity [64], but Cheonggukjang fermented with B. lichemiformis reduced body fat [50]. Cheonggukjang fermented with B. lichemiformis was more effective in increasing insulin-stimulated glucose uptake in 3T3-L1 adipocytes and glucose-stimulated insulin secretion in insulinoma cell than that made with B. subtilis [64]. Yang et al [50] also observed that Cheonggukjang fermented with B. subtilis and B. amylofenices had less antidiabetic activity than Cheonggukjang fermented with B. lichemiformis.…”
Section: Antiobesity Effects Of Fermented Soypastes In Rodentsmentioning
confidence: 89%
“…In traditionally made Cheonggukjang, B. subtilis is the major microorganism, but B. amylofenices and B. lichemiformis may also be present. Cheonggukjang fermented with B. subtilis and B. amylofenices had no effect on body weight or adiposity [64], but Cheonggukjang fermented with B. lichemiformis reduced body fat [50]. Cheonggukjang fermented with B. lichemiformis was more effective in increasing insulin-stimulated glucose uptake in 3T3-L1 adipocytes and glucose-stimulated insulin secretion in insulinoma cell than that made with B. subtilis [64].…”
Section: Antiobesity Effects Of Fermented Soypastes In Rodentsmentioning
confidence: 96%
See 1 more Smart Citation
“…Anti-diabetic effect was intensively studied with colleagues (D.J. Kwon et al, 2006Kwon et al, , 2007aKwon et al, , 2007b; several animal studies and a few human studies have evaluated the effects of fermented soybeans on glucose metabolism as reviewed previously . We found that chungkukjang improves glucose homeostasis by enhancing hepatic insulin sensitivity and insulinotropic actions in 90% pancreatectomized rats, a type 2 diabetic animal model (Kwon et al, 2007a(Kwon et al, , 2007b.…”
Section: Chungkukjangmentioning
confidence: 99%